Peran Kegiatan Ekstrakurikuler dalam Pengembangan Minat dan Bakat Peserta Didik di SMP Swasta Katolik Maria Kanisia (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
Education plays a crucial role in developing students’ potential both academically and non-academically. One of the important efforts to support this development is through extracurricular activities, which provide opportunities for students to explore and enhance their interests and talents. This study aims to describe the role of extracurricular activities in developing students’ interests and talents at SMP Swasta Katolik Maria Kanisia. This research employed a qualitative descriptive approach to understand the phenomenon in its natural setting. The data were collected through structured observations and document analysis involving students and extracurricular supervisors. The findings reveal that extracurricular activities have been implemented in a structured and systematic manner, including both compulsory and optional programs such as scouting, choir, drum band, wall magazine, and handicrafts. These activities contribute positively to the development of students’ interests, talents, creativity, social skills, and self-confidence. The role of supervisors is also significant in guiding and motivating students throughout the activities. Despite some challenges related to time and scheduling, extracurricular programs have shown meaningful impacts on students’ holistic development. Therefore, improving program management and support systems is essential to maximize their effectiveness.